Determination Of The Amount Of Dowry At Lampung Traditional Marriage In A Review Of Fiqh Munakahat - Jamzuri Malik MD; Syamsu Madyan; Dzulfikar Rodafi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This article examines the determination of relatively high dowries (mahar/maskawin) in Lampung Melinting traditional marriages in East Lampung and their conformity with Islamic law and Indonesian marriage law. Using an empirical juridical approach, data were collected through interviews with traditional leaders, religious leaders, community figures, and married couples, supported by statutory and conceptual materials. The findings show that the amount and form of dowry are not fixed, but are negotiated through family deliberation, taking into account the groom’s economic capacity and the expectations of the bride’s family within local custom. A high dowry is perceived as a symbol of pride, social status, and the groom’s seriousness in building a household, but it may also trigger social pressure, land sales, and economic burden. From the perspective of Islamic jurisprudence, there is no minimum or maximum standard of dowry as long as it is lawful, valuable, and agreed upon willingly. The study concludes that the Lampung Melinting practice of determining dowry reflects a dynamic interplay between religious norms, state law, and living custom, which needs continuous contextualization in modern society and justice.